Role of the PhoPQ two-component regulatory system in the β-lactam resistance of Stenotrophomonas maltophilia. (19th March 2021) - Huang, Hsin-Hui; Wu, Bo-Kuan; Li, Li-Hua; Lin, Yi-Tsung; Yang, Tsuey-Ching
Abstract: Background: Stenotrophomonas maltophilia, an opportunistic pathogen, is intrinsically resistant to most β-lactams except ceftazidime and ticarcillin/clavulanate, due to the inducibly expressed L1 and L2 β-lactamases. A two-component regulatory system (TCS) allows organisms to sense and respond to changes in different environmental conditions. The PhoPQ TCS of S. maltophilia plays regulatory roles in antibiotic susceptibility, physiology, stress adaption and virulence. Inactivation of S. maltophilia phoPQ increases β-lactam susceptibility. Objectives: To elucidate the PhoPQ-regulating mechanism for β-lactam resistance. Methods: The candidate genes responsible for the ΔphoPQ -mediated β-lactam resistance compromise were identified by transcriptome analysis and verified by quantitative RT–PCR and complementation assay. Etest was used to assess β-lactam susceptibility. The phosphorylation level of the PhoP protein was determined by Phos-tag SDS-PAGE and western blotting. A β-lactam influx assay was used to investigate the influx efficiency of a β-lactam. Results: PhoPQ deletion down-regulated the expression of mltD1 and slt, attenuated the induced β-lactamase activity and then compromised the β-lactam resistance. Complementation of mutant phoPQ with mltD1 or slt genes partially reverted the induced β-lactamase activity and β-lactam resistance. The PhoPQ TCS was activated in logarithmically grown KJ cells and was further activated by low magnesium, but not by a β-lactam. However, low-magnesium-mediated PhoPQ activation hardly made an impact on β-lactam resistance enhancement. Furthermore, PhoPQ inactivation altered the outer membrane permeability and increased the influx of a β-lactam. Conclusions: The PhoPQ TCS is activated to some extent in physiologically grown S. maltophilia . Inactivation of phoPQ attenuates the expression of mltD1 and slt, and increases β-lactam influx, both synergically contributing to β-lactam resistance compromise.